Trimethylamine-N-oxide: a potential biomarker and therapeutic target in ischemic stroke - Liu, Yuan; Qu, Juan; Xu, Junjie; Gu, Aiming; Deng, Dezhi; Jia, Xiaodan; Wang, Baoxiang (Frontiers in Neurology, 2023)
Ischemic stroke is by far the most common cerebrovascular disease and a major burden to the global economy and public health. Trimethylamine-N-oxide (TMAO), a small molecule compound produced by the metabolism of intestinal microorganisms, is reportedly associated with the risk of stroke, as well as the severity and prognosis of stroke; however, this conclusion remains contentious. This article reviews the production of TMAO, TMAO’s relationship with different etiological types of ischemic stroke, and the possibility of reducing TMAO levels to improve the prognosis of ischemic stroke.